Crossing the line : racial passing in twentieth-century U.S. literature and culture - Wald, Gayle, 1965- (Duke University Press, 2000)
Examines constructions of racial identity through the exploration of passing narratives including Black Like Me and forties jazz musician Mezz Mezzrow's memoir Really the Blues.
Revision of the author's thesis (Ph. D.)--Princeton University, 1995.
Keywords: American prose literature -- 20th century -- History and criticism.; Passing (Identity) -- United States -- History -- 20th century.; American prose literature -- African American authors -- History and criticism.; Multiracial people in literature.; Passing (Identity) in literature.; African Americans in literature.; Group identity in literature.; Race in literature.; Prose américaine -- 20e siècle -- Histoire et critique.; Passing (Identité) -- États-Unis -- Histoire -- 20e siècle.; Prose américaine -- Auteurs noirs américains -- Histoire et critique.; Passing (Identité) dans la littérature.; Noirs américains dans la littérature.; Identité collective dans la littérature.; Race dans la littérature.; LITERARY CRITICISM -- American -- African American.; African Americans in literature; American prose literature; American prose literature -- African American authors; Group identity in literature; Passing (Identity); Passing (Identity) in literature; Race in literature; Multiracial people in literature; United States; Rassenverhoudingen.; Etnisch bewustzijn.; Letterkunde.; 1900-1999; Criticism, interpretation, etc.; History